Impact of Reminders on Children’s Cognitive Flexibility, Intrinsic Motivation, and Mood Depends on Who Provides the Reminders - Qu, Li; Ong, Jing Y. (Frontiers in Psychology, 2016)
Reminding children to think about alternatives is a strategy adults often use to promote children’s cognitive flexibility, as well as children’s engagement in and enjoyment of the task. The current study investigated whether the impacts of reminders on kindergarten children’s cognitive flexibility, intrinsic motivation, and mood are moderated by who provides the reminders. Eighty-three healthy 5-year-old kindergarten children were randomly assigned to 2 (Reminder: No reminders vs. Reminders) X 2 (Agent: Tester vs. Partner) conditions. Children’s cognitive flexibility was measured via the Block Sorting Task (Fawcett & Garton, 2005; Garton & Pratt, 2001). Children reported their motivation and mood before Block Sorting, after practicing for Block Sorting, and after the actual Block Sorting. Children’s intrinsic motivation was measured by evaluating children’s choices during a period of free play after Block Sorting. The results revealed that, depending on who provides the reminders, reminding children of alternatives can influence kindergarten children’s performance on Block Sorting, children’s intrinsic motivation, and children’s self-reported mood.